2018
DOI: 10.1038/gim.2017.254
|View full text |Cite
|
Sign up to set email alerts
|

MSH6 and PMS2 germ-line pathogenic variants implicated in Lynch syndrome are associated with breast cancer

Abstract: PurposeAn association of Lynch syndrome (LS) with breast cancer has been long suspected; however, there have been insufficient data to address this question for each of the LS genes individually.MethodsWe conducted a retrospective review of personal and family history in 423 women with pathogenic or likely pathogenic germ-line variants in MLH1 (N = 65), MSH2 (N = 94), MSH6 (N = 140), or PMS2 (N = 124) identified via clinical multigene hereditary cancer testing. Standard incidence ratios (SIRs) of breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
5
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 31 publications
6
108
5
2
Order By: Relevance
“…15 Testing of incident endometrial cancers for MMR deficiency, as has been adopted widely for CRC, may provide a more effective strategy to identify path_MSH6 families. 16 Recently reported significant increases in breast cancer risk in MSH6and PMS2-associated LS 17 were not confirmed in this study. Based on the differences in cancer risks associated with the four path_MMR genes, we propose that LS should now be considered as a generic term for four clinically distinct inherited cancer risk syndromes.…”
Section: Discussioncontrasting
confidence: 60%
“…15 Testing of incident endometrial cancers for MMR deficiency, as has been adopted widely for CRC, may provide a more effective strategy to identify path_MSH6 families. 16 Recently reported significant increases in breast cancer risk in MSH6and PMS2-associated LS 17 were not confirmed in this study. Based on the differences in cancer risks associated with the four path_MMR genes, we propose that LS should now be considered as a generic term for four clinically distinct inherited cancer risk syndromes.…”
Section: Discussioncontrasting
confidence: 60%
“…74,75 In an analysis of 50,000 women who underwent multigene panel testing at a commercial laboratory, 423 women were identified with a molecular diagnosis of LS and found to have a 2-to 3-fold increased risk of agestandardized breast cancer when mutations were in the MSH6 (standard incidence ratio [SIR], 2.11; 95% CI, 1.56-2.86) and PMS2 (SIR, 2.92; 95% CI, 2.17-3.92) genes. 76 The authors of this study suggest that women with MSH6-or PMS2-associated LS may benefit from increased breast cancer screening. Further studies in less biased populations are necessary to replicate this finding before definitive recommendations can be made for increased or advanced breast screening in LS.…”
Section: Risk-reducing Medicationsmentioning
confidence: 88%
“…Win et al [6] conducted a systematic review on breast cancer in LS and identified 8 studies reporting an elevated (2-18-fold) risk, whereas the remaining 13 studies found no significantly increased risk. Moreover, breast cancer risk has been reported to be specifically associated with certain MMR genes, including MLH1 (vs. MSH2 [7,8]), MSH2 [9], and MSH6 and PMS2 (vs. MLH1 and MSH2 [10,11]. Variability in results may reflect different methods of ascertainment, cohort sizes, ethnicity, or other factors.…”
Section: Research Papermentioning
confidence: 99%